2009
DOI: 10.1093/cvr/cvp273
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism of ryanodine receptor modulation by FKBP12/12.6, protein kinase A, and K201

Abstract: The results are explained through a model proposing that phosphorylation and K201 acted similarly to change the conformation of RyR1/2 and regulate FKBP12/12.6 binding. K201 stabilized the conformation, whereas phosphorylation facilitated a subsequent molecular event that might increase the rate of an open/closed conformational transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…Previous reports indicated that K201 strengthens FKBP12.6 binding to RyR2 and FKBP12.6 is a requirement for K201-induced channel gating stabilization of RyR2 in myocytes (Yano et al, 2003;Wehrens et al, 2005). In vitro studies, however, suggest that K201 increasing FKBP12.6 rate of dissociation from RyRs (Blayney et al, 2010). Here, we tested if the effect of K201 on RyRs could be related to FKBP12.6 dissociation.…”
Section: Effects Of K201 On Ryrs and Sercamentioning
confidence: 96%
See 1 more Smart Citation
“…Previous reports indicated that K201 strengthens FKBP12.6 binding to RyR2 and FKBP12.6 is a requirement for K201-induced channel gating stabilization of RyR2 in myocytes (Yano et al, 2003;Wehrens et al, 2005). In vitro studies, however, suggest that K201 increasing FKBP12.6 rate of dissociation from RyRs (Blayney et al, 2010). Here, we tested if the effect of K201 on RyRs could be related to FKBP12.6 dissociation.…”
Section: Effects Of K201 On Ryrs and Sercamentioning
confidence: 96%
“…Two studies assessed the effects of K201 on the RyR isoform 1 (RyR1). In one study, K201 was found to slightly decrease or increase [ 3 H] ryanodine binding to purified and solubilized RyR1 in the absence or presence of physiologic levels of Mg 21 , respectively (Blayney et al, 2010). The other study described a K201-induced increase in SR Ca 21 release from microsomes (Almassy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal ventricular myocytes were obtained and cultured as described previously [9] . Briefly, myocytes were obtained and cultured in 20% FBS-DMEM culture medium with BrdU to suppress the growth of fibroblasts.…”
Section: Cell Culturementioning
confidence: 99%
“…FKBP12.6 also plays a role in the molecular mechanisms underlying severe arrhythmias and cardiac insufficiency [8] . CPVT may be the conse- [9] . FKBP12.6/12 dissociation from the binding site at RyR2 is likely due to a decrease in affinity, but this hypothesis is still controversial [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Others have studied isolated RyR2 preparations and observed that not only phosphorylation at S2808, but also dephosphorylation, increased its open probability (9,11). Several groups have failed to reproduce the effect observed by Marks and colleagues (2) of PKA phosphorylation at S2808 or mutations of this site on FKBP12.6 binding (2, 10, 12, 13), but others have (14). Moreover, a recent study by the Bers group (10) reported very low FKBP12.6 concentrations in rodent cardiomyocytes, resulting in only 10%-20% of RyR2 being occupied by FKBP12.6.…”
Section: Figurementioning
confidence: 99%